Love martyrdom beyond the box - Lee, Hannah Elaine A.; Esponga, Leila M.; Libres, Krissia Anne H.; Lorque, Denize Ann Nicole B. (Parañaque City: Olivarez College, 2020)
Marriage martyrdom today features men and women dealing with either marital and paternal. When someone is considered a martyr, they would rather continue their suffering than address and fix the problem, because they think that it is okay to suffer. But the thought underlies among them every single day as to leave for their own sake thinking that it will be selfish for them to do so or continue to live with their partners. One of these concerns is knowing the reason why men can also be mistreated in marriage. Hence, the study investigated the factors of men while staying in an uncommon relationship set-up. The participants were husbands married in 3-15 years composed of six cases particularly a battered husband, a husband with a cheating wife, a husband with a barren wife, a house husband not by his own choice, a man in an arranged marriage, and a husband that has lost his love for his partner all being considered to be marital martyrs and does not choose to leave despite the situations. They shared their experiences first with a face-to-face interview followed by a focus group discussion. The key informant interview was used to ask specific experts or professionals who were able to share their knowledge and experiences in their respective fields. Aside from the participants, the researchers also invited another set of participants known to be students of Olivarez College to conduct a focus group discussion and acknowledge their insights regarding men as marital martyrs. In general, the result showed that despite the marital conflicts, the participants stayed in their current situation because of their love for their family. Awareness regarding men as marital martyrs should emerge and should be taken into consideration.
Undergraduate Thesis
Keywords: Marriage; Martyrdom; Male martyrs; Husbands